2014
DOI: 10.3409/fb62_3.219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Haplotype within the Promoter Region of the <I>MSTN</I> Gene in Horses from Five of the most Common Breeds in Poland

Abstract: Identification of a new haplotype within the promoter region of the MSTN gene in horses from five of the most common breeds in Poland. Folia Biologica (Kraków) $ : 219-222. Myostatin (GDF-8) encoded by the MSTN gene is a negative regulator of muscle growth and development and belongs to the TGF-â superfamily of secreted growth and differentiation factors. In Thoroughbred horses, an MSTN sequence polymorphism (g.66493737C>T) is associated with optimum race distance. In the present study, a genetic polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Analysis performed in this study showed that polymorphism g.66495826T 4C (also known as 26T 4C) is present in Hucul and Polish Heavy Draft populations, but is absent in Arabians and Konik Polski (Table 4), what was also previously reported (Stefaniuk et al, 2014a). Moreover, in this locus there is no significant deviation from Hardy-Weinberg equilibrium (p 40.05).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Analysis performed in this study showed that polymorphism g.66495826T 4C (also known as 26T 4C) is present in Hucul and Polish Heavy Draft populations, but is absent in Arabians and Konik Polski (Table 4), what was also previously reported (Stefaniuk et al, 2014a). Moreover, in this locus there is no significant deviation from Hardy-Weinberg equilibrium (p 40.05).…”
Section: Discussionsupporting
confidence: 56%
“…However, to date only a few studies have analyzed horse MSTN gene polymorphisms in different horse breeds and types (Dall'Olio et al, 2010;Baron et al, 2012;Li et al, 2014;Stefaniuk et al, 2014a). In this study, we analyzed a region of the MSTN gene (rev.str.66,495,489,608;chr.…”
Section: Introductionmentioning
confidence: 99%
“…The search for SNPs in several horse breeds revealed the presence of two modifications in the promoter region (summarized in Table 1), which are organized in four possible haplotypes: 1 (T 26 , −T 156 ), 2 (T 26 , −C 156 ), 3 (C 26 , −T 156 ) and 4 (C 26 , −C 156 ) [64, 65]. According to frequency studies, haplotype 1 could be the most ancestral one, since it was present in all studied breeds [64].…”
Section: Equine Mstn Gene Promotermentioning
confidence: 99%
“…The mutations or indels of MSTN have been shown to produce a double-muscling phenotype caused by muscular hyperplasia and hypertrophy in some of livestock species, such as cattle breeds (Belgian Blue, Piedmontese) (Grobet et al, 1997;McPherron and Lee, 1997;Kambadur et al, 1997;Miranda et al, 2002) and sheep (Texel sheep, East Friesian sheep) (Walling et al, 2004;Johnson et al, 2005;Clop et al, 2006;Bignell et al, 2010) and chickens (Gu et al, 2002 Furthermore, double-muscling is an autosomal recessive gene that can be inherited and it is occurred due to abnormal growth of muscles (Khaerunnis et al, 2016). A single nucleotide variation in intron region of the MSTN gene (g.66493737T>C) is using as a molecular marker for the breeding parameter such as race distance ability in horses and many morphological characters in livestock (Binns et al, 2010;Tozaki et al, 2010;2011;Hill et al, 2010a;2010b;2012a;2012b;Dall'Olio et al, 2010;Stefaniuk et al, 2014;Pereira et al, 2016;Işık et al, 2017;Tüten sevim et al, 2017;Cieslak et al, 2018). Many studies have been carried out MSTN gene polymorphisms in horses and its association with racing performances and body condition but in donkeys, there were a few published articles till now (Bertolini et al, 2015;Tozaki et al, 2010;2011;Hill et al, 2010a;2010b;2012a;2012b;Dall'Olio et al, 2010;Stefaniuk et al, 2014;Pereira et al, 2016;Cieslak et al, 2018;Dong-hua et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide variation in intron region of the MSTN gene (g.66493737T>C) is using as a molecular marker for the breeding parameter such as race distance ability in horses and many morphological characters in livestock (Binns et al, 2010;Tozaki et al, 2010;2011;Hill et al, 2010a;2010b;2012a;2012b;Dall'Olio et al, 2010;Stefaniuk et al, 2014;Pereira et al, 2016;Işık et al, 2017;Tüten sevim et al, 2017;Cieslak et al, 2018). Many studies have been carried out MSTN gene polymorphisms in horses and its association with racing performances and body condition but in donkeys, there were a few published articles till now (Bertolini et al, 2015;Tozaki et al, 2010;2011;Hill et al, 2010a;2010b;2012a;2012b;Dall'Olio et al, 2010;Stefaniuk et al, 2014;Pereira et al, 2016;Cieslak et al, 2018;Dong-hua et al, 2017). Overall, in terms of growth, development, and performance in domesticated animals MSTN gene has a significant role.…”
Section: Introductionmentioning
confidence: 99%